Transnational governance in global finance - the principles for stable capital flows and fair debt restructuring in emerging markets - Raymond Ritter (European Central Bank (ECB), 2009)
This paper analyses and assesses the track record and effectiveness of the so-called “Principles for Stable Capital Flows and Fair Debt Restructuring in Emerging Markets”,which have emerged as an important instrument for crisis prevention and crisis resolution in the international financial system. The paper argues that, notwithstanding their low profile, the Principles which were jointly agreed between sovereign debtors and their private creditors in 2004 have proved to be an effective instrument in spite of their voluntary and nonbinding nature. Indeed, an increasing number of sovereign debtors and private creditors have adopted the Principles' recommendations on transparency and the timely flow of information, close dialogue, “good faith” actions and fair treatment. Two elements have been critical to the success of the Principles: (i) their specific design feature as a soft mode of governance agreed by a transnational public-private partnership and (ii) the “hardening” after their launch in terms of precision and delegation, thus moving them somewhat along the continuum of soft law and hard law towards the latter. The paper also makes the case that the Principles and their design features can provide some lessons for the current international policy debate on codes of conduct in global financial regulation..
Keywords: F34; F51; F53; G15; G18; 330; Crisis prevention; debt restructuring; sovereign default; soft law; transnational public-private partnership; global financial governance.; Kapitalmobilität; Internationale Staatsschulden; Öffentlich-private Partnerschaft; Internationaler Finanzmarkt; Schwellenländer